Etika Komunikasi Islam Dalam Media Sosial - Abdullah, Abdullah; Kahina, Dwi Iin (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2022)
Current technological developments, especially informatics and communication have reached a golden point, one of which is social media. This is evidenced by human activities, which range from children, teenagers to the elderly who are completely dependent on social media and have become a necessity of their life. Social media has quite a lot of positive impacts on people's lives, but it can also have negative impacts if its users are too excessive. Therefore, the self-awareness of media users is very important to be improved and supported by ethics or Islamic teachings in social media. This is considering that what is media content will be able to influence self-image and affect the relationships that exist with other parties. Freedom of opinion, the freedom of sharing offered by social media should be addressed wisely by paying attention to Islamic ethics in social media. The purpose of writing this paper is to analyze how the ethics of social media in the Islamic view. The writing method uses literature review with reference to several sources, both primary and secondary sources originating from several books, the Koran, al-Hadith and journals. Based on the results of the paper analysis, it can be concluded that a Muslim in socializing using social media should always uphold ethics in socializing and respecting fellow creatures of Allah, because every deed done in this world will be accounted for in the hereafter. The benefits of social media are quite a lot to seek the blessing of Allah SWT, depending on its use, whether it is used for good or bad things.